Traumatic brain injury: from the ball field to the battlefield - Faden, Alan (Henry Stewart Talks, 2011)
Heterogeneity of traumatic brain injury, Concussion, Mild TBI, Neurocognitive testing, Brain physiology is related to recovery, Post-concussion symptoms, Effects of repetitive sports concussion, Gender and recovery, Age and recovery, Chronic neurodegeneration, Complexity of blast effects, Pathways of secondary injury in TBI, Genomics and CNS injury, Recommended design criteria for pre-clinical evaluation of pharmacological agents for TBI, Laser targeted strategies, Multipotential treatment, In vitro models, Improving likelihood of successful clinical trials